Pengaruh Biosaka dan Pupuk Hayati BRE4 terhadap Pertumbuhan dan Produksi Tanaman Pakcoy (Brassica rapa L.) Serta Pemanfaatannya sebagai Booklet - Sabrina Aulia Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the effect of biosaka and BRE4 biofertilizer on the growth and yield of pakcoy (Brassica rapa L.) as well as to develop the research findings into a booklet-based information media. Pakcoy is a horticultural crop belonging to the Brassicaceae family with high economic value and increasing demand in Indonesia. However, efforts to increase pakcoy production often rely on the excessive use of chemical fertilizers, which may have negative environmental impacts. Therefore, the application of biosaka and BRE4 biofertilizer is proposed as a more environmentally friendly alternative in crop cultivation. The research was conducted from June to October 2025 in the Greenhouse of Agrotechnopark and Laboratory of Biology Education Study Program, University of Jember. This study employed of factorial Completely Randomized Design with two factors, namely : biosaka (0, 3, 6, 9, ml/L of water) and BRE4 biofertilizers (0, 5, 10, 15 ml/L of water) each treatment with three replications. Observed parameters included plant height, growth rate, number of leaves, leaf area, fresh weight, dry weight, consumable weigh, and harvest index. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at 5% significance level. The result showed that the most effective treatment in improving the growth and yield of pakcoy was biosaka at a concentration of 6 ml/L of water combined with BRE4 biofertilizer at 15 ml/L of water. Abiotic factors such as soil pH, temperature, and humidity within optimal ranges during the study. The educational product produced in the form of a booklet was deemed suitable for use as an information resource for the general public. Therefore, biosaka and BRE4 biofertilizer can be recommended as an alternative for optimal pakcoy cultivation.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Biological elicitor; booklet; liquid biofertilizer; organic farming.